Association between weight-adjusted waist circumference index and myocardial infarction: results from the national health and nutrition examination survey, 1999–2014 - Yu, Jian-hong; Yin, Ming-gang (Frontiers in Cardiovascular Medicine, 2024)
BackgroundWeight-adjusted waist circumference index (WWI) is a novel index related to obesity and has been associated with the risk and prognosis of several diseases. The aim of the study was to determine the association between WWI and myocardial infarction.MethodsThe study analyzed cross-sectional data from 31,535 participants derived from the 1999–2014 National Health and Nutrition Examination Survey (NHANES) dataset. Multiple logistic regression and restricted cubic spline (RCS) analyses were conducted to assess both linear and nonlinear associations between WWI and myocardial infarction. Subgroup analyses and interaction tests were also performed.ResultsAmong the 31,535 participants analyzed, 1,449 (4.82%) had experienced a myocardial infarction. The fully adjusted models demonstrated a positive association between WWI and myocardial infarction [odds ratio (OR) = 1.34, 95% confidence interval (CI): 1.13–1.58]. Individuals in the highest quartile of WWI were 81% more likely to suffer from a myocardial infarction compared to those in the lowest quartile (OR = 1.81, 95% CI: 1.24–2.63). The analysis employing restricted cubic spline modeling indicated a nonlinear positive correlation between WWI and myocardial infarction. The risk of myocardial infarction was 1.29 times higher when WWI was below 10.97 cm/√kg (OR = 2.29, 95% CI: 1.37–3.84). When WWI exceeded 10.97 cm/√kg, the upward trend in the risk of myocardial infarction significantly slowed with increasing WWI (OR = 1.26, 95%CI:1.03–1.56). A threshold WWI value of greater than 11.15 cm/√kg was identified for predicting myocardial infarction, outperforming waist circumference and body mass index (BMI). Subgroup analyses revealed that the impact of WWI on myocardial infarction varied across different populations. Interaction analyses demonstrated significant interactions between myocardial infarction incidence and WWI with age, hypertension, coronary heart disease, angina pectoris, and stroke (P for interaction <0.05), but not with gender, race, obesity, diabetes, or prediabetes and heart failure (P for interaction >0.05).ConclusionsThe findings suggest that there is a positive and non-linear association between WWI and the incidence of myocardial infarction. We recommend incorporating WWI into routine physical examinations and cardiovascular risk screening as an early warning mechanism. This may facilitate early identification of high-risk individuals and promote earlier preventive interventions.